Suppression of Staphylococcus epidermidis Skin Wound Infection by Citrus aurantifolia Lime Peel Ethanolic Extract: A Concentration-Response Analysis - Putri, Amalia Eka; Santoso, Arif; Ginaris, Rifkarosita Putri (CV. Nusantara Scientific Medical, 2023)
Staphylococcus epidermidis is a coagulase-negative Staphylococcus (CoNS) that causes a spectrum of superficial skin infections including wound infections, folliculitis, and burn-associated skin sepsis, particularly through its capacity to form highly resistant biofilms. The emergence of methicillin-resistant S. epidermidis (MRSE) with polysaccharide intercellular adhesin (PIA)-mediated biofilm has severely limited available therapeutic options. This study assessed the concentration-dependent bacteriostatic activity and minimum inhibitory concentration (MIC) of Citrus aurantifolia lime peel ethanolic extract against S. epidermidis ATCC 12228 using the Kirby-Bauer disc diffusion method on Muller Hinton Agar (MHA). Extract from lime peels sourced in Tulungagung, East Java was prepared by ethanol maceration. Fourteen concentrations (0.5–150 mg/mL) were tested in triplicate. The MIC was 1 mg/mL (inhibition zone 6.73 ± 0.06 mm). Inhibition zones increased progressively from 6.73 mm (MIC, 1 mg/mL) to 11.60 ± 0.35 mm (150 mg/mL), with the very strong threshold (>10 mm) first crossed at 70 mg/mL. Concentration-response linearity was confirmed (R² > 0.97). The positive control (tetracycline 30 µg) produced 28.17 ± 0.59 mm. These findings establish a pharmacological basis for incorporating lime peel extract into wound care and topical antiseptic formulations targeting S. epidermidis.